2019
DOI: 10.1080/00268976.2019.1607917
|View full text |Cite
|
Sign up to set email alerts
|

The influence of random pinning on the melting scenario of two-dimensional soft-disk systems

Abstract: We present the results of a computer simulation study of the melting scenario of two-dimensional soft-disk systems with potential U (r) = ε(σ/r) n , n = 12 and n = 1024, both in the presence of random pinning and without it. The melting parameters have been determined from analysis of the behavior of equations of state, correlation functions of the orientational and translational order parameters, Young modulus and renormalization group equations. The transition points obtained from these criteria are in good … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…At high temperatures, the effect of attraction should vanish, and only the repulsive branch of potential (1) should play a more significant role. Indeed, analyzing the melting scenarios of triangular crystals at high temperatures (and high densities), we observed that LJ12m systems demonstrated the same melting scenarios as soft disks repulsive potential 1/r 12 (the third melting scenario 14,42,45 ).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…At high temperatures, the effect of attraction should vanish, and only the repulsive branch of potential (1) should play a more significant role. Indeed, analyzing the melting scenarios of triangular crystals at high temperatures (and high densities), we observed that LJ12m systems demonstrated the same melting scenarios as soft disks repulsive potential 1/r 12 (the third melting scenario 14,42,45 ).…”
Section: Resultsmentioning
confidence: 91%
“…The obtained results agree well with the melting scenario for repulsive disks 1/r 12 (reported in Refs. 14,42,45 ), but do not exhibit two continuous BKT transitions in the LJ system at high temperatures 12,89 . The obtained results agree well with the melting scenario for repulsive disks 1/r 12 (reported in Refs.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In computer simulations [51][52][53][54][55] and in experiments [56] it was shown that the system could melt through a continuous BKT type solid-hexatic transition, but the hexatic-liquid transition is of the first order. In paper [54] (see also [57,58]) a detailed study of a soft disk system with potential U (r) = (σ/r) n was presented. It was shown that the system melted in accordance with the BKTHNY scenario for n ≤ 6, while for n > 6 a two-stage melting transition took place with a continuous solid-hexatic and first-order hexatic-liquid transition.…”
Section: Introductionmentioning
confidence: 99%